Anwāʿu al-Naʿt wa Aghrāḍuhu fī Kitāb Durūs al-Lughah al-ʿArabiyyah li Imām Zarkashiy wa Imām Syubbāniy - Suryadarma, Yoke; Saidah, Mandrasi Amira; Yolanda, Fidela Devi (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2024)
The book "Durusul Lughoh al-Arabiyah" is an Arabic learning book that is used widely in Indonesia, especially in Pesantren Modern. There are many discourses on Morphology (Nahwu) in this book that is interesting to be seen deeply. One of these discourses is an-na’tu. This article wants to analyze the various kinds of an-Na'tu and their objectives in the book "Durusul Lughoh al-Arabiyah" juz 1 written by Imam Zarkasyi and Imam Syubbani. The objectives of this research are: To know the sentences in which there are an-Na'tu in the book "Durusul Lughoh al-Arabiyah", and to know the kinds of an-Na'tu and their purpose in that book. Researchers used qualitative research with descriptive methods. To get the data, Researchers used documentation as well as using content analysis to analyze the data. The results obtained by the researcher are: 1) the sentences in which there are an-Na'tu in the book "Durusul Lughoh al-Arabiyah" there are 286 sentences. 2) The types are an-Na'tu al-haqiqi al-mufrod 266 sentences, an-Na'tu al-haqiqi al-jumlah al-ismiyah 13 sentences, and an-Na'tu al-haqiqi syibhu al-jumlah 7 sentences. From this result, perhaps this article will be one of the resources to explore the discourses of Morphology (Nahwu) in this book.